Reattachment of fractured maxillary incisors using fiber-reinforced post: Two case reports - Tosun, Gul; Yildiz, Esma; Elbay, Mesut; Sener, Yagmur (European Journal of Dentistry, 2012)
Objective: The reattachment of the crown fragment to a fractured tooth is a conservative treatment that should be considered for young patients with crown-root fractures to the maxillary incisors if the subgingival fracture can be exposed to provide isolation. Gingivectomy, the surgical or orthodontic extrusion of the apical fragment is necessary to expose the subgingival fracture. This report demonstrates the treatment of two cases with the combination of gingivectomy or resective osseous surgery, reattachment of coronal fracture and fiber-reinforced polymer posts and shows three years long term follow-up. Subgingivally extended crown-root fractures of maxillary incisors were restored with a combination of chemically cured resin material, light cured resin material and polyethylene fiber.Conclusion: Within the limitations of this case report, it was demonstrated that reattachment of tooth fragments can successfully benefit periodontal health, aesthetic needs and normal functioning after three years. (Eur J Dent 2012;6:227-233)
Keywords: Crown-root fracture; fiber post; reattachment